2023
DOI: 10.1021/acsnano.2c09744
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow Energy Domain Wall Device for Spin-Based Neuromorphic Computing

Abstract: Neuromorphic computing (NC) is gaining wide acceptance as a potential technology to achieve lowpower intelligent devices. To realize NC, researchers investigate various types of synthetic neurons and synaptic devices, such as memristors and spintronic devices. In comparison, spintronics-based neurons and synapses have potentially higher endurance. However, for realizing low-power devices, domain wall (DW) devices that show DW motion at low energies�typically below pJ/bit�are favored. Here, we demonstrate DW mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 100 publications
1
12
0
Order By: Relevance
“…As stated in section 2, the length of our simulated device (the ferromagnetic layer in which the domain wall moves) is 1000 nm and the width is 100 nm. Our device dimensions are about one order lower than that of the domain-wall devices experimentally demonstrated thus far [26,29,31,32]. Also, they are of comparable size as the domain-wall devices reported through simulation [31], if they have to store synaptic weights of the same bit resolution.…”
Section: Scaling Issuesmentioning
confidence: 75%
See 1 more Smart Citation
“…As stated in section 2, the length of our simulated device (the ferromagnetic layer in which the domain wall moves) is 1000 nm and the width is 100 nm. Our device dimensions are about one order lower than that of the domain-wall devices experimentally demonstrated thus far [26,29,31,32]. Also, they are of comparable size as the domain-wall devices reported through simulation [31], if they have to store synaptic weights of the same bit resolution.…”
Section: Scaling Issuesmentioning
confidence: 75%
“…So estimating non-linearity and asymmetry factors for Leonard et al's reported data is difficult. Kumar et al have recently reported synaptic behaviour in a similar domain-wall device through magneto-optic Kerr effect (MOKE) images and change in TMR of the MTJ structure due to current-driven domain-wall motion [32]. But they have not reported any LTP-LTD plot from which the non-linearity and asymmetry coefficients can be inferred.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, Kumar et al studied the hybrid high pressure‐W/low pressure‐W spin‐Hall layer and demonstrated the DW motion at ultralow current densities of 10 6 A m −2 . [ 51 ] A small assisting OOP magnetic field is required to move the DWs at such low current densities. Such a low‐current density is attributed to the moderate SHA values of 0.15 and ultralow pinning field of 2 mT.…”
Section: Spin–orbit Torquementioning
confidence: 99%
“…[ 50 ] Kumar et al demonstrated the synaptic functionality in meander devices. [ 51 ] In the meander device, two segments of DW devices join at an offset that forms the pinning site. The number of multiple resistances is determined by the number of pinning sites.…”
Section: Spintronic Devices For Neuromorphic Applicationsmentioning
confidence: 99%
“…Along with charge‐based devices, synaptic devices exploiting their spin degree of freedom have been studied recently. [ 11,12,13,14 ] Devices based on spin‐transfer‐torque magnetic random memory (STT‐MRAM), [ 15,16 ] skyrmion, [ 17–19 ] and spin‐orbit‐torque magnetic random memory (SOT‐MRAM), [ 20,21,22 ] etc have been implemented in synaptic electronics. The spintronics materials are appealing for their fast switching, unlimited endurance and compatibility with the complementary metal oxide semiconductors (CMOS) based technology.…”
Section: Introductionmentioning
confidence: 99%